2018
DOI: 10.1148/radiol.2017170458
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Risk Category and Screening Round on the Performance of an MR Imaging and Mammography Screening Program in Carriers of the BRCA Mutation and Other Women at Increased Risk

Abstract: Purpose To evaluate the real-life performance of a breast cancer screening program for women with different categories of increased breast cancer risk with multiple follow-up rounds in an academic hospital with a large screening population. Materials and Methods Screening examinations (magnetic resonance [MR] imaging and mammography) for women at increased breast cancer risk (January 1, 2003, to January 1, 2014) were evaluated. Risk category, age, recall for workup of screening-detected abnormalities, biopsy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 30 publications
4
27
1
2
Order By: Relevance
“…Strigel et al only reported a higher incidence of node‐positive invasive cancers, albeit this was a much smaller study . Vreemann et al showed that performance of screening is highly dependent on the actual screening indication . For example, the sensitivity of the screening program was only 81% in BRCA1 carriers, whereas it exceeded 90% for all other indications, which is likely an effect of the fast growth of cancers in these women.…”
Section: Quality Of Screeningmentioning
confidence: 99%
See 4 more Smart Citations
“…Strigel et al only reported a higher incidence of node‐positive invasive cancers, albeit this was a much smaller study . Vreemann et al showed that performance of screening is highly dependent on the actual screening indication . For example, the sensitivity of the screening program was only 81% in BRCA1 carriers, whereas it exceeded 90% for all other indications, which is likely an effect of the fast growth of cancers in these women.…”
Section: Quality Of Screeningmentioning
confidence: 99%
“…It is important to realize that this is no longer true, even when studies are still presenting MRI as a supplemental test . The incremental cancer detection with mammography ranges from 0–19.4% . However, the study by Sung et al reports on MRI and mammography examinations that were not simultaneously obtained and should therefore likely be disregarded in this sense .…”
Section: Supplemental Screening Techniquesmentioning
confidence: 99%
See 3 more Smart Citations